PENERAPAN KONSEP ENJOYFULL LEARNING MENGGUNAKAN MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR KIMIA PADA MATERI HUKUM-HUKUM DASAR KIMIA DAN STOIKIOMETRI (PENELITIAN TINDAKAN KELAS DI MAN 1 GROBOGAN) - Moh Muthohir; Mukhoyyarotul Jannah; Fujiama Diapoldo Silalahi (STEKOM PRESS, 2020)
This research, in general, aims to improve the learning outcomes of class X MIPA 4 students of MAN 1 Grobogan in the 2018/2019 academic year by implementing multimedia learning. And specifically it aims to make students able to achieve the learning objectives by producing a minimum KKM score of 70 and at least 80% of the total students are able to reach this minimum limit. The research method used in this research is the Classroom Action Research Method or better known as the Classroom Action Research (PTK) method. The PTK method is a process of assessing learning problems in the classroom through self-reflection in an effort to solve these problems by taking planned actions in real situations and analyzing any effects of these treatments. The results of research conducted on class X MIPA 4 MAN 1 Grobogan, the application of multimedia presentation learning media on the basic laws of chemistry and stoichiometry with the concept of enjoyful learning can improve student learning outcomes. That the application of multimedia presentation learning media can improve student learning outcomes in chemistry, especially in the material of the basic laws of chemistry and stoichiometry